A −80 dB PSRR 4.99 ​ppm/°C TC bandgap reference with nonlinear compensation. (January 2020) - Liang, Jian; Yi, Shuiping; Bai, Wenlong; Wang, Lidan; Zhan, Chenchang; Liao, Congwei; Lam, Hing-Mo; Zhang, Min; Zhang, Shengdong; Jiao, Hailong
Abstract: A precision bandgap reference (BGR) with high power supply ripple rejection (PSRR) and low temperature coefficient (TC) is proposed for the peripheral compensation circuitry of active-matrix organic light-emitting diode (AMOLED) displays. The PSRR is enhanced by a coupling structure of the power supply and a feedback loop of the start-up circuit. Furthermore, a high-order nonlinear compensation method is proposed to reduce the temperature coefficient by utilizing the systematic nonlinear offset voltage within the bandgap circuit. Measurement results of the proposed BGR implemented in an industrial 0.25-μm CMOS process demonstrate a TC of 4.99 ​ppm/°C in a wide temperature range of −40 ​°C–130 ​°C. A PSRR around −80 dB is also achieved by the proposed circuit at low frequency.